Levosimendan in acute heart failure with severely reduced kidney function, a propensity score matched registry study - Rottmann, Felix; Breiden, Ann Katrin; Bemtgen, Xavier; Welte, Thomas; Supady, Alexander; Wengenmayer, Tobias; Staudacher, Dawid (Frontiers in Cardiovascular Medicine, 2022)
Patients with heart failure frequently present with kidney dysfunction. Kidney function is relevant, as prognosis declines with reduced kidney function and potentially beneficial drugs like levosimendan are contraindicated for missing safety data.Materials and methodsA single-center retrospective registry study was conducted including all patients receiving levosimendan on a medical intensive care unit between January 2010 and December 2019. Exclusion criteria were a follow-up less than 24 h or missing glomerular filtration rate (eGFR) before administration of levosimendan. The first course of treatment was evaluated. Patients were stratified by eGFR before drug administration and the primary endpoint was a composite of supraventricular-, ventricular tachycardia and death within 7 days after administration of levosimendan. An internal control group was created by propensity score matching.
Gesehen am 25.01.2023